UPAYA KEJAKSAAN DALAM PENGEMBALIAN ASET NEGARA SEBAGAI HASIL DARI TINDAK PIDANA KORUPSI - Darmukit Darmukit (Jurnal Hukum, 2020)
The prosecutor's office carries out the task of prosecuting and returning something that has become a state asset that has been seized by corruptors. This study aims to determine the process of investigating corruption cases at the Pemalang District Attorney and to find out the prosecutors' efforts to recover state assets as a result of corruption. The method used is a sociological juridical approach, because the problems studied are closely related to social reality and real human behavior. This research tries to explore in-depth and in real terms a phenomenon of the application of criminal law from a social context. The results of this study are 1) The process of investigating corruption at the Pemalang District Attorney General is regulated in the Regulation of the Attorney General of the Republic of Indonesia Number 039 / A / JA / 2010, dated 29 October 2010 concerning Technical Administrative Governance for Special Crime Case Handling, namely in Chapter VI concerning Investigation. The process of investigating criminal acts of corruption is carried out in stages: a) Issuance of Investigation Warrants, Notification of Commencement of Investigation and Notification of Investigation, b) Plans of Investigation, c) Summons of Witnesses, Experts, and Suspects, d) Application for examination permission to officials authorized, e) Examination of Witnesses, Experts, and Suspects, f) Actions of search and / or confiscation, g) Detention of suspects and h) Other actions of the investigation team according to responsible law and 2) The efforts of the District Attorney to recover state assets / state finances from The results of the criminal act of corruption are carried out in stage a) Investigation, namely the existence of an act of confiscation of the assets of the perpetrator of the crime of corruption, b) Prosecution, namely in the prosecution against the perpetrator of a criminal act of corruption in which the Public Prosecutor must state / sue a criminal fine and money. compensation for assets acquired by perpetrators of criminal corruption, mention, and c) the stage of execution in which the Attorney General's Office immediately executes the assets belonging to the perpetrator of the criminal act of corruption after the Court Decision has permanent legal force.